Reusable launchers - Berry, W. (Cranfield University, 1993)
This research on Reusable Launchers was motivated by the need to reduce substantially the cost of space transportation. The specific objective was to- explore the perception that launcher reusability is the key to achieving these major cost reductions. The exploration was achieved by undertaking a comparative system study on potentially feasible reusable launcher concepts, using a consistent set of design tools, a standard analysis methodology and a standard reference mission. To set the background f or the research, the results of an extensive literature review are 'presented on the vehicle studies and technology developments that are engaged across the world on reusable launchers. Comprehensive vehicle studies appear to be engaged without justification for the choice of selected concepts in the absence of results from comparative system studies of reusable launchers. Technology developments also appear to be engaged without clear links to needs derived from vehicle system studies. The challenge of reusability is then addressed. Firstly, to set the performance and cost targets of reusable launchers, the capabilities of current expendable launchers are derived. Secondly, to establish the operational requirements for reusable launchers, the probable space transportation needs for the early 21st century are derived. Thirdly, the concepts and characteristics of reusable launchers are derived, allowing the selection, on a rationale basis, of a short-list of 13 potentially feasible reusable launcher concepts for analysis in the research. The performance equations of reusable launchers are 'then derived, leading to the preparation of the comparative analysis tools. The major work-of the research, which ''comprises the performance analysis, technical feasibility assessment and cost"analysis of each candidate vehicle are, then presented and compared-. A set of acceptance requirements for performance,, technical feasibility and operational costs - of reusable launchers is then -derived. The results of the comparative analysis for each candidate launcher are then measured , against these requirements. The results of the comparative analysis show that only 2 of the' 13 candidate reusable launcher concepts are able to meet all the acceptance'requirements. These two acceptable vehicles are both rocket-propelled. They are, ýin order of preference: a single-stage-to-orbit, rocket-propelled, vertical launch and vertical landing vehicle; a two-stage-to-orbit, rocket-propelled, vertical launch and horizontal landing vehicle. The operational ''costs per launch for these two'vehicles,, based on a utilisation plan of 3 vehicles operating for 20 years at a launch rate of 12 launches per year, was calculated to be about 20 % of the current costs of the European Ariane 44L expendable launcher. This warrants their further evaluation in a thorough feasibility study. The more complex, air-breathing propelled, horizontal launch and landing vehicles were found to be unable to meet the performance, technical feasibility and cost requirements: Several vehicles were found to be unable to deliver a positive payload mass to orbit; Several vehicles were found to have technology requirements that were deemed to be infeasible to achieve; Several vehicles were found to have operational costs ranging from equal to double that -of the European Ariane 44L expendable launcher,, which -was- adopted as a comparative reference vehicle. The contributions of this research to the advancement of knowledge on reusable launchers are: a clear identification of the performance, capability limits of 13 plausible reusable launcher concepts; an analysis methodology for determining the performance capability limits for any reusable launcher concept; a clear identification of the reasons. for the poor practical performance of air-breathing propulsion systems for Earth-to-orbit launchers, which results from their installed operational characteristics.